2021
DOI: 10.1021/acsami.1c09200
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Solid Polymer Electrolyte with High Ion Conductivity and Super Stretchability for All-Solid Zinc-Ion Batteries

Abstract: The zinc-ion battery (ZIB) is a novel energy storage device, an attractive alternative to the lithium-ion battery. The frequently used aqueous electrolyte suffers from many problems such as zinc dendrites and leakage, which prompts hydrogel electrolytes and solid electrolytes as good replacements. However, hydrogel electrolytes are usually unstable, owing to water volatilization. Herein, a novel solid polymer electrolyte (SPE) utilizing coordination of zinc ions is designed and then introduced into an all-soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 59 publications
1
36
0
Order By: Relevance
“…To realize it, one way is to blend different kinds of monomer composition to synthesize the composite polymers with optimized performance. [16][17][18][19] For example, Zhou et al reported a high ionic conductivity composite hydrogel electrolyte composed of guar gum, sodium alginate, and ethylene glycol. [20] Besides that, the other effective method is to introduce the nanofiller into the polymer matrix, which is expected to improve the ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…To realize it, one way is to blend different kinds of monomer composition to synthesize the composite polymers with optimized performance. [16][17][18][19] For example, Zhou et al reported a high ionic conductivity composite hydrogel electrolyte composed of guar gum, sodium alginate, and ethylene glycol. [20] Besides that, the other effective method is to introduce the nanofiller into the polymer matrix, which is expected to improve the ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, most works have been dedicated to the exploration of cathode materials to improve the ZIBs performance, including manganese-based oxides, , vanadium-based oxides, prussian blue analogues, polyanion compounds, , and organic compound materials . Although breakthroughs on the exploration of cathode materials for ZIBs have been achieved, the problems of Zn metal anodes including Zn dendrites, Zn corrosion/hydrogen evolution, and surface passivation, still seriously hinder the overall performance of ZIBs. , …”
Section: Introductionmentioning
confidence: 99%
“…The temperature dependencies of σ can be fitted with the Vogel–Tammann–Fulcher (VTF) equation. 33 where σ 0 is the ionic conductivity at infinite temperature, E a is the activation energy, and T 0 is the temperature at which molecular motion is frozen. Parameters of the VTF fitting are provided in Table S3 (ESI†).…”
Section: Resultsmentioning
confidence: 99%